Scientific Statistics, Teaching, Learning and the Computer - Box, George (My University, 1996)
It is argued that the domination of Statistics by Mathematics rather than by Science has greatly reduced the value and the status of the subject. The mathematical "theorem - proof paradigm" has supplanted the "iterative learning paradigm" of scientific method. This misunderstanding has affected university teaching, research, the granting of tenure to faculty and the distributions of grants by funding agencies. Possible ways in which some of these problems might be overcome and the role that computers can play in this reformation are discussed.